Surgery for giant emphysematous bullae: case report and a short literature review - Huang, Wenting; Han, Rui; Li, Li; He, Yong (Journal of Thoracic Disease, 2014)
Giant bullous emphysema (GBE), known as ‘vanishing lung syndrome’, usually occurs in association with chronic obstructive pulmonary disease (COPD). In this report, we describe a patient with giant emphysematous bulla occupying approximately 95% of the right hemithorax, who had history of repeated attacks of acute exacerbation of COPD. About 95% of right pulmonary parenchyma was removed. Delightfully, the 5% of residual lung compressed for 4 years gradually inflated, and occupied the whole hemithorax. Preoperatively he was functionally and clinically severely disabled while improved markedly after bullectomy.